Analisis Trend Kinerja Terhadap ROE Dan ROI Pada PT. Telkom Indonesia (Persero) Tbk Yang Merujuk Pada Surat Keputusan Menteri BUMN No. Kep-100/MBU/2002 - Alma Alia Syahra; Anwar Bowo Leksono; Suseno Hendratmoko (STIKes Ibnu Sina Ajibarang, 2023)
This research aims to analyze the trend of changes in the ROE and ROI ratios at PT Telkom Indonesia (Persero) Tbk which refers to the BUMN Decree KEP-100/MBU/2002 seen from the ROE and ROI profitability ratios for the 2017-2021 period. This type of research is descriptive research that uses quantitative data methods to analyze, calculate and interpret study results. This data is obtained from financial reports that have been published on the Indonesia Stock Exchange or IDN Financial. The results of research analysis of the ROE profitability ratio in 2017-2021 PT Telkom Indonesia (Persero) Tbk experienced a significant decline from 2017 to 2018, but was quite stable in the following years although it still experienced increases and decreases, although not too significant. The results of the research analysis of the ROI profitability ratio in 2017-2021, PT Telkom Indonesia (Persero) Tbk experienced a significant decline from 2017 to 2018, and continued to fall until 2020, but in 2021 it increased, although not significantly.